Web Usage Mining Analysis in “OLX Autos” Online Sales Applications - Raden Aries Sofwan Zarkasih (Jurnal Mantik, 2021)
Olx Autos is an online car selling service that allows customers to sell their cars quickly/instantly to more than 2,000+ partners. OLX Autos has 100+ inspection locations in 7 major cities in Indonesia, namely Greater Jakarta, Bandung, Semarang, Yogyakarta, Surabaya, Bali and Medan. Restful web service is a standard for exchanging data between applications or systems. This research analyzes restful web services to integrate the OLX Autos system with suppliers and buyers. Thus, making it easier for OLX Autos to place car orders and making it easier for suppliers to receive car orders. This study uses descriptive qualitative research methods, the results of the study explain that the Restful Web Service method used can integrate the OLX Autos system with buyers and suppliers very easily.